Ship-borne atmospheric methane measurements during MOSAiC Leg 4-5 - Amanda Sellmaier; Ellen Damm; Torsten Sachs; Falk Pätzold; Daiki Nomura; Markus Rex (PANGAEA, 2025)
This dataset contains minute-averaged CH4 concentrations and its isotopic composition (δ13C-CH4) in air above the Arctic Ocean measured during Leg 4 (4 June 2020 – 12 August 2020) and Leg 5 (12 August 2020 – 12 October 2020) of the MOSAiC expedition. The continuous ship-borne measurements were recorded by Cavity Ring-Down Spectroscopy (CRDS) using a Picarro G2132-i isotope analyser (Picarro, Inc., Santa Clara, USA). Air was drawn in from the starboard side of compass deck of RV Polarstern at about 21 m above the sea-ice and ocean surface using a Teflon tube with a length of 75 m and an inside diameter of 4.5 mm. A flow rate of 2.4 l min-1 was generated with a 3KQ Diaphragma pump (Boxer, Ottobeuren, Germany). The Picarro G2132-i isotope analyser then continuously measured in the "High Precision" mode with 1 Hz temporal resolution. To identify and flag local pollution in the data sets, the Pollution Detection Algorithm (PDA) developed by Beck et al. (2022) was applied to the raw concentration data. The PDA employs a five-step statistical filter to detect and flag contaminated measurement points, which were subsequently removed from the concentration and isotopy data. Using this approach, 17.3 % of the raw data were identified as polluted and removed from the time series. The data columns include the Date and Time in Coordinated Universal Time (UTC), the latitude and longitude of the Research Vessel Polarstern, the methane concentration in ppm and the isotopic composition of CH4 (δ13C-CH4) in extperthousand.